Physical performance in young judo athletes: Influence of somatic maturation, growth, and training experience - Detanico, D.; Lima Kons, R.; Fukuda, D. H.; Teixeira, A. S. (Research Quarterly for Exercise and Sport, 2020)
Purpose: To determine the individual contributions of chronological age, somatic maturation, body size and composition, and training experience as indicators of performance in neuromuscular and judo-specific assessments in young athletes. Methods: Sixty-six youth judo athletes performed anthropometric measurements, neuromuscular tests—standing long jump test (SLJ), medicine ball throw test (MBT), handgrip strength test (HGS), and judo-specific tests—Special Judo Fitness test (SJFT) and Judogi Grip Isometric Strength Test (JGSTISO). A multiple linear regression was used with the level of significance set at 5%. Results: The main results showed age-peak height velocity (PHV), body fat and training experience explained close to 20% of SJFT performance. Chronological age, age-PHV, height, body mass and body fat accounted for 42% of variance in JGSTISO. Chronological age, body fat and training experience explained 35% of the variance in SLJ, while chronological age, body mass and body fat explained 53% of the variance in MBT. Finally, age-PHV, body mass and height explained 54% of the variance in HGS. Conclusion: Estimated age-PHV and growth variables explained moderate to large proportions of the variance in neuromuscular tests (with exception of SLJ), while both estimated age-PHV, training and growth variables were predictors of judo-specific performance.